Lysosomal Targeted Cyclometallic Iridium(Ⅲ) Salicylaldehyde-Coumarin Schiff Base Complexes and Anticancer Application - Xu, Ruixi; Wu, Yuting; Liu, Zhe; Liu, Jinfeng; Liu, Xicheng (Frontiers in Chemistry, 2022)
Natural coumarin derivatives and cyclometallic iridium (Ⅲ) (IrⅢ) complexes have attracted much attention in the field of anticancer. In this study, six coumarin-modified cyclometallic IrⅢ salicylaldehyde Schiff base complexes ([(ppy)2Ir(O^N)]/[(ppy-CHO)2Ir(O^N)]) were designed and synthesized. Compared with coumarin and IrⅢ complex monomers, target complexes exhibited favorable cytotoxic activity toward A549 and BEAS-2B cells. These complexes could induce extensive apoptosis of A549 cell (late apoptosis), which was represented by the disturbance of cell cycle (G1-phase) and the accumulation of intracellular reactive oxygen species, exhibiting an anticancer mechanism of oxidation. With the help of suitable fluorescence of these complexes, no conflict with the probes, confocal detection confirmed that complexes showed an energy-dependent cellular uptake mechanism and triggered lysosome-mediated apoptosis in A549 cell line. Above all, our findings reveal the design of a lysosomal targeting cyclometallic IrⅢ Schiff base complexes and provide a new idea for the design of integrated drugs for diagnosis and treatment.